Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.jnutbio.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of parental zinc deficiency on metal homeostasis and embryonic development in a zebrafish model

Abstract: The high prevalence of zinc deficiency is a global public health concern, and suboptimal maternal zinc consumption has been associated with adverse effects ranging from impaired glucose tolerance to low birthweights. The mechanisms that contribute to altered development and poor health in zinc deficient offspring are not completely understood. To address this gap, we utilized the Danio rerio model and investigated the impact of dietary zinc deficiency on adults and their developing progeny. Zinc deficient adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 69 publications
(74 reference statements)
2
14
0
Order By: Relevance
“…11 As observed in mammals, specific nutrients and dietary ingredients, or the lack thereof, can potentially alter physiology, behavior, and/or molecular pathways in zebrafish, [12][13][14][15][16][17][18][19][20][21][22][23][24][25] whereas other researches suggested that nutrient content of diets fed to adult zebrafish can even influence the development and health of their offspring. [26][27][28][29][30][31] All these evidences suggest that for zebrafish, diet is an important environmental factor that can potentially compromise and confound outcomes related to the question of study; Therefore, a lack of nutritional control in zebrafish laboratories could affect the interpretation of both past and future research. 32 At present, a wide variety of commercial diets is utilized in zebrafish research laboratories, and in some cases, include live animal supplementation (paramecia, rotifers, and brine shrimp) during early or other life stages.…”
Section: Introductionmentioning
confidence: 99%
“…11 As observed in mammals, specific nutrients and dietary ingredients, or the lack thereof, can potentially alter physiology, behavior, and/or molecular pathways in zebrafish, [12][13][14][15][16][17][18][19][20][21][22][23][24][25] whereas other researches suggested that nutrient content of diets fed to adult zebrafish can even influence the development and health of their offspring. [26][27][28][29][30][31] All these evidences suggest that for zebrafish, diet is an important environmental factor that can potentially compromise and confound outcomes related to the question of study; Therefore, a lack of nutritional control in zebrafish laboratories could affect the interpretation of both past and future research. 32 At present, a wide variety of commercial diets is utilized in zebrafish research laboratories, and in some cases, include live animal supplementation (paramecia, rotifers, and brine shrimp) during early or other life stages.…”
Section: Introductionmentioning
confidence: 99%
“…All adult animals were fed standard lab diet (Gemma Micro. Skretting, Tooele, France) until 8 weeks post fertilization when they were moved to clean enclosures, randomized to either zinc deficient or zinc adequate diets, and housed at densities of ~6 fish / liter as previously described [ 34 ]. The zebrafish diets were produced as previously described [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Skretting, Tooele, France) until 8 weeks post fertilization when they were moved to clean enclosures, randomized to either zinc deficient or zinc adequate diets, and housed at densities of ~6 fish / liter as previously described [ 34 ]. The zebrafish diets were produced as previously described [ 34 ]. Feeding volumes for all feeds were ~5% body weight / day, or until satiation, given over 2–3 feedings in a day depending on life stage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By day 14, most of the genes impacted by zinc supplementation returned to basal expression levels. Beaver et al provided zinc-deficient diets to zebrafish and looked at the impact on their offspring [93]. Embryos produced by those receiving the zinc-deficient diets had increased embryonic mortality and malformations of the snout and eyes.…”
Section: Nutrition-related Studiesmentioning
confidence: 99%